The Analysis of Students and Teachers Readiness On Distance Learning Mathematics In New Normal - Ratnadewi Ratnadewi (STAI Miftahul Ula Nganjuk, 2021)
A sudden pandemic has created a learning system in Indonesia, which is usually done face-to-face, in the New Normal era, online learning is required. This sudden incident turned the wheel of life and learning 180 degrees. This paper discusses the level of readiness of students and teachers in mathematics distance learning. The level of readiness includes ownership of electronic devices, availability of internet signals, costs, support from parents or people around, skills in accessing digital learning applications, learning places, teachers who can teach well, materials, teacher guidance, solutions if they encounter problems, abstinence give up, and be able to understand distance learning material. Data obtained from the results of questionnaires and interviews with students and teachers in Indonesia. The results of the analysis of the data obtained are that students and teachers are in the criteria of being quite ready to be very ready to carry out distance learning. From the results of questionnaires and interviews, both students and teachers prefer a mixture of distance and face-to-face learning, because when it is difficult to understand the learning material, the teacher can explain directly, more able to monitor the condition of students. The weakness of distance learning is that it is constrained by internet signals, no emotional bonds, it is difficult to monitor students' abilities and higher credit costs.